Quantification and characterization of microplastics in mangrove clams, Anodontia edentula (Linnaeus 1758) and Geloina expansa (Mousson 1849), in Tabango, Leyte - Ramirez, Bien Leo R.
The mangrove ecosystem acts as a trap and basin for plastic pollution. Diverse organisms that depend on this ecosystem are now more exposed to the effects of plastics, but the extent is not fully measured yet. This study therefore attempted to contribute to the knowledge of microplastic pollution in the mangrove ecosystem by quantifying the concentration of microplastics in mangrove clams, Anadontia edentula (Linnaeus 1758) and Geloina expansa (Mousson 1849) and in the sediments of the mangrove forests in Tabango, Leyte. A total of 348 microplastic particles were collected in 51 individuals (63.75%) of A. edentula and 61 individuals (76.25%) of G. expansa. A. edentula samples were only collected in Sites 1 and 2 which had 1.28 plus or minus 1.67 MP/individual (0.092 plus or minus 0.301 MP/g) and 1.63 plus or minus 1.68 MP/individual (0.216 plus or minus 0.324 MP/g), respectively. Meanwhile, G. expansa samples were only collected in Sites 3 and 4 which had 2.08 plus or minus 2.67 MPs/individual (0.259 plus or minus 0.379 MP/g) and 3.73 plus or minus 4.73 MP per individual (0.250 plus or minus 0.404 MP/g), respectively. Additionally, the microplastic abundance in the sediments indicates that Site 4 had the most microplastics per gram of sediment with 0.125 MP/g, followed by Site 3 (0.100 MP/g), then Site 1 (0.098 MP/g), and finally by Site 2 (0.060 MP/g). Fibers and fragments microplastics were prevalent in both clam tissues and sediments across all sites with blue, white, and transparent colors composing most of the particles. There were many small-sized MP (0.01 to 0.50 mm) in clams while larger-sized MPs (0.5 to 5.00mm) were common in the sediments. Furthermore, the number of microplastics in the tissues only had a very weak to negligible correlation to the shell dimensions, total weight, and soft tissue weight of the clams. Overall, microplastics are ubiquitous in both biota and sedimets in the mangrove forests of Tabango, Leyte and this study suggests incorporating these clam species in future studies to understand more about its potential to be bioindicators for MP abundance in the mangrove ecosystem.